Monitoring of Flood Dynamics Using Multi Temporal Satellite Data: A Case Study of Kerala Floods 2018 - Faheed, Jasin K. P.; Yusuf, Alia; Manjusree, P.; Ansari, Ziaur Rehman (European Journal of Applied Sciences, 2022)
India is one of the worst flood affected country in South East Asia and accounts for one fifth of global death count due to floods. It causes heavy losses to property, infrastructure, agriculture, land and overburdens the country’s budget and resources. Around 40 million hectares of land in the country are subjected to floods according to National Flood Commission, and an average of 18.6 million hectares of land is affected annually. During 2018, Kerala was hit by two flood events in July and August. In August, 2018, Kerala experienced the worst ever floods in its history since 1924. The torrential rains triggered several landslides and forced the release of excess water from 37 dams across the state, aggravating the flood impact. The devastating floods and landslides caused extensive damage to houses, roads, railways, bridges, power supplies, communications networks, and other infrastructure. Satellite Remote Sensing has made substantial contribution in flood monitoring and damage assessment. The unique capabilities of satellites to provide comprehensive, synoptic and multi-temporal coverage of very large areas at regular interval and with quick turnaround time have been very valuable in monitoring and managing flood dynamics. The microwave region of the EM spectrum has a greater potential in identification of flooded areas because of almost all weather capability. In this study, multi-temporal microwave SAR data from RADARSAT and SENTINEL-1 satellites was used to map the flood affected areas in Kerala and to capture the dynamics of the spatial flood extent. The analysis showed maximum flood inundation in the second flood event in August. A steady recession of flood was observed in the July flood event. The peak flooding was observed on 18th August 2018. There is a rapid progression of flood from August 11th to August 18th 2018 after which, a slight recession was observed from August 18th to 21st ,2018. The flood could be seen slightly progressing in the next interval of August 21st to 24th ,2018 after which, again an overall recession in the spatial flood could be observed by 27th August 2018. Kottayam, Pathanamthitta and Alappuzha were some of the worst flood affected districts. The maximum flood affected district is observed to be Alappuzha with a maximum flood inundated area of 27691hectares on 18 August 2018. In the district of Alappuzha a steady progression in the flood is observed after 21 August. Whereas in the other two districts namely Kottayam, Pathanamthitta the flood is found to be receeding after August 24, 2018. This study demonstrated the potential of multi-temporal satellite imageries for capturing the flood dynamics in a spatial domain. The progression and recession maps can be used for relief management by the disaster managers on the ground.